The current status of hypertensive patients and medicine use at the geriatric - cardiology department - Tue Tinh hospital in 2023 - Pham, Thuy Phuong; Hoang, Trong Quan; Vũ, Minh Hieu; Nguyễn, Phạm Ngọc Mai (Tạp chí Y Dược cổ truyền Việt Nam, 2026)
Objective: To survey on the current status of hypertensive patients and the use of medicine to treat hypertension at the Geriatric - Cardiology Department - Tue Tinh Hospital. Research subjects and methods: A cross-sectional, retrospective and analysis conducted research was conducted on 389 medical records diagnosed with hypertension for outpatient and inpatient treatment at the Department of Geriatrics - Cardiology - Tue Tinh Hospital from January 2023 to the end of December 2023. Results: In the 389 researched medical records, the mean patient age was 77.8 ± 6.5 years, with the 70–79 age group accounting for the highest proportion (43%) and those under 50 the lowest (4%). Female patients comprised 62%, higher than males (38%), and 78% had age-related risk factors. Five main classes of antihypertensive drugs were used-Angiotensin-Converting Enzyme inhibitors (ACEi), Angiotensin II Receptor Blockers (ARBs), calcium channel blockers (CCB), beta-blockers (BB), and diuretics—all consistent with national treatment guidelines. Monotherapy was more commonly prescribed than combination therapy in both initial (59.1%) and final regimens (52.7%). The rate of achieving target blood pressure was high (88%), approximately seven times greater than the failure rate (12%). Conclusions: The research sample had an average age of 77.8 ± 65.4 years, mainly from 70-79 years old (43%). The rate of women is 1.5 times higher than that of men. Study of 389 records with 5 groups of antihypertensive drugs. In both therapies, the rate of use of monotherapy regimens was higher than the rate of use of multitherapy regimens. Combinations of 2 to 4 drugs showed different distributions, with beta-blockers being most common in the 3-drug combination group.